Sense of belonging, intra-organizational relations and active participation in community development: an analysis of medium-sized manufacturing companies in Mexico (2020)
Causal relations between sense of belonging, intra-organizational relationships and active participation in community development are analyzed in this article, which is an explanatory investigation. The analytical tool measures sense of belonging, intraorganizational relationships and active participation in community development using seventeen items on a sample of one hundred ninety-three workers from five medium-sized manufacturing companies in Mexico. Results seem to indicate positive causal relations between sense of belonging and intraorganizational relationships, and also between intraorganizational relationships and active participation in community development. This is a contribution for a better understaning of the relationships among the components of organizational culture, organizational citizen behavior and corporate social responsability.